Effect of Neurofeedback and Electromyographic-Biofeedback Therapy on Improving Hand Function in Stroke Patients. Issue 2 (March 2014) - Rayegani, S. M.; Raeissadat, S. A.; Sedighipour, L.; Mohammad Rezazadeh, I.; Bahrami, M. H.; Eliaspour, D.; Khosrawi, S.
Abstract : Purpose : The aim of the present study was to evaluate the effect of applying electroencephalogram (EEG) biofeedback (neurobiofeedback) or electromyographic (EMG) biofeedback to conventional occupational therapy (OT) on improving hand function in stroke patients.Methods: This study was designed as a preliminary clinical trial. Thirty patients with stroke were entered the study. Hand function was evaluated by Jebsen Hand Function Test pre and post intervention. Patients were allocated to 3 intervention cohorts: (1) OT, (2) OT plus EMG-biofeedback therapy, and (3) OT plus neurofeedback therapy. All patients received 10 sessions of conventional OT. Patients in cohorts 2 and 3 also received EMG-biofeedback and neurofeedback therapy, respectively. EMG-biofeedback therapy was performed to strengthen the abductor pollicis brevis (APB) muscle. Neurofeedback training was aimed at enhancing sensorimotor rhythm after mental motor imagery.Results : Hand function was improved significantly in the 3 groups. The spectral power density of the sensorimotor rhythm band in the neurofeedback group increased after mental motor imagery. Maximum and mean contraction values of electrical activities of the APB muscle during voluntary contraction increased significantly after EMG-biofeedback training.Conclusion : Patients in the neurofeedback and EMG-biofeedback groups showed hand improvement similar to conventional OT. Further studies are suggested to assign the best protocol for neurofeedback and EMG-biofeedback therapy.